2011
DOI: 10.1038/onc.2011.343
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 regulates MYCN mRNA stabilization and translation in human neuroblastoma cells

Abstract: The MYCN gene plays a critical role in determining the clinical behavior of neuroblastoma. Although it is known that genomic amplification occurs in high-risk subsets, it remains unclear how MYCN expression is regulated in the pathogenesis of neuroblastomas. Herein, we report that MYCN expression was regulated by the oncoprotein MDM2 at the post-transcriptional level and was associated with neuroblastoma cell growth. Increasing MDM2 by ectopic overexpression in the cytoplasm enhanced both mRNA and protein expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 35 publications
(50 reference statements)
8
69
0
1
Order By: Relevance
“…Aurora A is a negative prognostic factor and a potential therapeutic target in neuroblastoma (46), which, according to our recent study, is a bona fide p53 target (38). In addition, RITA treatment leads to the decrease of MDM2, which upregulates N-Myc (17). Taken together, our data suggest that reactivation of p53 by RITA causes inhibition of N-Myc via induction of its E3 ligase Fbxw7.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Aurora A is a negative prognostic factor and a potential therapeutic target in neuroblastoma (46), which, according to our recent study, is a bona fide p53 target (38). In addition, RITA treatment leads to the decrease of MDM2, which upregulates N-Myc (17). Taken together, our data suggest that reactivation of p53 by RITA causes inhibition of N-Myc via induction of its E3 ligase Fbxw7.…”
Section: Discussionsupporting
confidence: 60%
“…p53 dysfunction in neuroblastoma has been linked to MDM2 amplification and Wip1 activation (5,14), as well as to homozygous deletions of CDKN2A, encoding MDM2 inhibitor p14ARF (15). Moreover, N-Myc inactivates p53 by inducing the expression of MDM2 (16), which in turn upregulates N-Myc (17). p53 mutations occur very seldom in neuroblastoma, but in cell lines established at relapse p53 mutations are more frequent, implicating mutant p53 in the development of therapy-resistant phenotype (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to confirm that MDM2 and MYCN reciprocally regulate p53, we tested the effect of siMDM2 on p53 expression in SHEP-Tet/21N line with overexpression of MDM2 and with conditional expression of ectopic MYCN that was not regulated by MDM2 due to lack of original 3'UTR. 19,20 We found that the expression of p53 was induced by siMDM2 in both SHEP-Tet/21N in the presence of tetracycline (without MYCN expression) and SHEP-Tet/21N in the absence of tetracycline (with MYCN expression), with higher levels of basic expression and induction of p53 in the latter than in the former (Fig. 3D).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 86%
“…MDM2, when translocated from the nucleus to the cytoplasm, binds to the AU-rich elements of the MYCN 3'-UTR and regulates MYCN mRNA stabilization and its translation. 19 Because MDM2 and MYCN are not only mutually regulated but also reciprocally regulate p53 in neuroblastoma, we are interested in investigating exactly how that cross talk between MYCN and the MDM2/p53 signaling pathway leads to individual expression of those molecules in neuroblastoma cells, and importantly, what is the impact of that cross talk on neuroblastoma cell growth and induction of apoptosis. In the present study, we selected neuroblastoma cell lines with or without MYCN gene amplification that either have or do not have MDM2 overexpression, and utilized gene transfection and gene knockdown by siRNA to carry out our investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Sucrose gradient polysome fractionation was performed as described in Gu et al (2012), with some modifications. ES cells grown in 15-mm plates in 2i medium (5 3 10 7 cells per plate) were incubated with 100 mg/mL cycloheximide (Sigma) for 15 min to arrest ribosome movement on mRNAs.…”
Section: Polysome Fractionationmentioning
confidence: 99%